Jubileusz 90 rocznicy urodzin oraz 65 rocznicy święceń kapłańskich o. prof. Hugolina Langkammera - Kowalski, Marcin (The Biblical Annals, 2020)
Jubilee of the 90th Birthday and the 65th Anniversary of the Priestly Ordination of Fr. Prof. Hugolin Langkammer